Managerial Attitudes on Environmental Reporting: Evidence from Croatia - Krivačić, Dubravka; Janković, Sandra (Journal of Environmental Accounting and Management, 2026)
Environmental responsibility is an important element of business sustainability. It is operationalised through environmental accounting and reporting, which have become inevitable management tools in modern business. International reporting frameworks, legislation, and the requirements of stakeholders, necessitate thinking about environmental information which businesses should report. Decisions on reporting environmental information is associated with managerial attitudes and expectations. The lack of research, especially in European countries, on the importance of environmental reporting for a company’s management, is the reason for conducting this study. Therefore, the main objective of the research was to investigate managerial attitudes regarding the importance of environmental information for companies stakeholders. A survey was used to collect data. The analysis of the distribution of managers’ responses shows that most respondents believe environmental information is part of corporate social responsibility. From the standpoint of the companies it is ethical to collect and report environmental information. Through the factor analysis of managerial attitudes, research indicates variables of the highest importance in the extracted factor: the usefulness of environmental information for different stakeholders, the importance of exploring stakeholders’ interests, and the importance of ensuring the quantity and quality of environmental information. The extracted factor, labelled as “the importance of environmental reporting” was further defined as a dependent variable in a simple linear regression model in which industry and size of the company were defined as independent variables. Research identifies only the industry of the company as positively and significantly related to dependent variable.